Gejala Klinis Ehrlichiosis Pada Pasien Anjing Di Yogyakarta - Yustinus Oswin Primajuni Wuhan; Ida Tjahajati; Aris Haryanto (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Canine monocytic ehrlichiosis is a potentially fatal disease in dogs and requires an early diagnosis to start therapy properly so that it produces a good prognosis. The research was conducted to determine ehrlichiosis in Yogyakarta based on clinical, hematological, and molecular diagnoses using the gltA gene. A total of 51 dog patients who were suspected of ehrlichiosis were performed anamnesis, clinical examination, then blood samples were taken for molecular examination with PCR. The molecular examination results of dog patients who were positive for ehrlichiosis based on PCR were 33.3% (17/51), with clinical symptoms which were 58.8% weak (10/17), 47% anorexia (8/17), 47% (8/17) gastrointestinal disorders (diarrhea and vomiting), 41.1% (7/17) pale mucosa, 35.2% (6/17) tick infestation, 35.2% (6/17) fever, 29,4% (5/17) dehydration, 11.7% (2/17) bleeding. The conclusion of this study is that the clinical of patients with erhlichiosis are very varied.